A Case of a Fibrous Omphalomesenteric Duct Remnant Causing an Intestinal Obstruction in an Adult - Tonneau, Camille; Herve , Jerome; Nebbot, Benjamin; Cappeliez, Olivier; Pather, Sanjiva; Saliba, Thomas (Acta medica Lituanica, 2024)
The omphalomesenteric canal (OMC) is an important embryonic structure that normally regresses during development. OMC remnant persistance is rare and can lead to complications such as small intestinal obstruction. We report the case of an 18-year-old male with flu-like symptoms, abdominal pain, fever, and a positive McBurney sign. A CT scan raised the suspicion of occlusion, prompting surgery, revealing a fibrous band from the umbilicus to the mesocolon around which the right colon and caecum were wrapped. OMC anomalies are generally encountered in children, with a large spectrum of possibilities causing various problems. Diagnosis is challenging, with symptoms often mimicking other conditions, often necessitating surgery to obtain a definitive diagnosis. Intestinal obstruction is a severe complication, necessitating urgent surgical resection. Radiological imaging mainly serves to prompt surgical intervention as it is limited in directly visualizing fibrous bands, with surgery remaining the best way to obtain a diagnosis, as well as allowing concomitant treatment.
Keywords: omphalomesenteric duct; abdominal surgery; emergency; adult; occlusion; case report